HUBUNGAN JARAK KELAHIRAN DAN POLA PENGASUHAN DENGAN STATUS GIZI ANAK BALITA DI WILAYAH KERJA PUSKESMAS KECAMATAN TANJUNG TIRAM KABUPATEN BATU BARA TAHUN 2013 - trisya maya ginting; Evawany Y Aritonang; Mhd.Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
It is noted highly rate population growth in Indonesia, to respond it, the government adoptthe Family Planning (KB) as a strategic program nationally since 1970. This program is referredmainly to those new and fertilized couples to have own arrange interval of birth. The family withmany children may influence the quality care and this is going to impact on nutritional status forunderfive children. The objective of this study is to determine the correlations of arrange timeinterval of birth and the caring pattern with the nutritional status of the underfive children in theterritory Tanjung Tiram Sub district Community Health Centers in Batu Bara District for 2013.This study adopted a descriptive method with cross sectional design. The population of thisresearch involved 4.883 underfive children. The data was gathered for November 2013 usingquestionnaire, interview them directly about their daily practicing in feeding the underfive childrenand how to care. About the sample, to take them in purposively and the sample was assessed inproportional allocation and choose them systematic random sampling, further the data wasanalyzed by using a distribution frequency table and total sample involved 94 underfive children.The result indicated that the interval of birth 2 years with nutritional status noted 14.3% iscategorized malnutrition, 85.7% is categorized less nutrition whereas with interval of birth > 2years noted 87.1% is normal. The caring pattern based on practiced meal feed more is notedmalnutrition category is noted 82.1% whereas caring health with moderate category is noted81.4%.By this research is suggested to the health worker keep improving public knowledge aboutthe KB program and encourage the mothers given counseling how to enrich nutritional status forunderfive children. This recommendation emphasized feeding practices, health status up andhygiene as well as.Keywords : interval of birth, caring pattern, nutritional status, underfive children